2022
DOI: 10.31729/jnma.7124
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the Inferior Alveolar Canal by Mandibular Third Molar among Images Taken from Patients Visiting Dental Imaging Centres of Kathmandu: A Descriptive Cross-sectional Study

Abstract: Introduction: Third molars are common teeth to be impacted. The position of mandibular third molar is such that it is in close contact with inferior alveolar canal which may lead to nerve damage during its removal. So, this study was conducted to find out the prevalence of compression of inferior alveolar canal by mandibular third molars. Methods: This descriptive cross-sectional study was conducted on images collected from Dental Imaging Centers of Nepal from 25th June 2020 to 15th February 2021 after obtaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…16 Previous studies conducted on the Korean, Indian, Nepali, and German populations found a close approximation of IANC to the roots of the lower 3rd molar in 28.3%, 67%, 46.8%, and 58% of the cases, respectively. [17][18][19][20] Studies have supported the sexual dimorphism of the IANC canal, especially in the Southern and Eastern Indian populations. 21,22 In addition, a study conducted in the United States reported that third molars were significantly closer to IANC in women than in men.…”
Section: Discussionmentioning
confidence: 96%
“…16 Previous studies conducted on the Korean, Indian, Nepali, and German populations found a close approximation of IANC to the roots of the lower 3rd molar in 28.3%, 67%, 46.8%, and 58% of the cases, respectively. [17][18][19][20] Studies have supported the sexual dimorphism of the IANC canal, especially in the Southern and Eastern Indian populations. 21,22 In addition, a study conducted in the United States reported that third molars were significantly closer to IANC in women than in men.…”
Section: Discussionmentioning
confidence: 96%